PENDAMPINGAN REMAJA SEKEHA TRUNA TRUNI (STT) DI MASA COVID-19 SEBAGAI “KADER SEHAT BERBUDAYA” DALAM PROMOSI KESEHATAN REPRODUKSI - Widarini, N.P.; Subrata, M.; Suariyani, L.P.; Kurniasari, M.D. (Buletin Udayana Mengabdi; Vol 21 No 3 (2022): Buletin Udayana Mengabdi, 2022)
Health promotion in adolescents can be done through educational approaches such as sex education with lecture methods, group discussions, seminars, simulations, theater, regional performances, and others. Bali has a lot of local wisdom as a medium for health promotion, one of which is STT youth who are members of the custom. STT is a forum for youth associations to develop youth. STT, which has been prepared as the next generation in preserving customs and culture in Bali, can also play a role in improving adolescent reproductive health. The purpose of this activity is to train and assist youth cadres in promoting adolescent reproductive health. The method of activity is in the form of lectures, question and answer discussions, giving pre-post test questionnaires and role play for reproductive health promotion. The results of the activity showed an average increase in knowledge and attitudes before and after counseling was carried out by 0.6 and 2.44. The p-values are 0.018 and 0.006 (<0.05), which means that there is a significant difference before and after the training. Conclusions and implications are expected that the results of this activity youth cadres as cultured healthy cadres can play an active role in promoting adolescent reproductive health.   Keywords: cultured healthy cadres, youth, health promotion, reproductive health, covid-19